(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the reading process in children from a neuropsycholinguistic perspective. The main focus is on the relationship between reading speed and text comprehension processes. The neuropsycholinguistic foundations of the “DonoQiz-Uz” test are also analyzed, and its sensitivity in identifying phonological processing, semantic comprehension, and decoding processes in children is substantiated through examples.